Exploring English Education Students' Perceptions and Practices of Using TikTok for English Learning - Shinta Liana; Muhammad Yunus; Dwi Fita Heriyawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the perceptions and practices of English education students toward the use of TikTok as a medium for learning English. As digital platforms increasingly shape students' daily lives, especially among Generation Z, TikTok's potential as an informal learning tool warrants scholarly attention. However, limited research explores how English education students perceive and apply it in their language learning, particularly within Indonesian higher education contexts. Therefore, this study aims to identify students' attitudes toward TikTok and describe how they integrate the platform into their English learning routines. Grounded in Mobile-Assisted Language Learning (MALL) theory, social constructivism, and the principles of learner autonomy and digital literacy, this mixed-method study involved 12 second-semester English education students at Universitas Islam Malang. The purposive sample size was determined based on saturation principles appropriate for qualitative research, consistent with thematic analysis methodology. Data were collected through online questionnaires and semi-structured interviews with four selected participants. Thematic analysis examined students' perceptions, preferred content, strategies, and challenges in using TikTok for English learning. Findings revealed that all 12 students (100%) perceived TikTok as a valuable tool for vocabulary acquisition, while 11 students (92%) considered it educationally useful. Students generally viewed TikTok positively as an enjoyable, flexible, and motivating platform, with 83% reporting enhanced motivation to learn English. They accessed English content related to vocabulary, pronunciation, grammar, and speaking during leisure time, adopting strategies such as saving videos, rewatching content, mimicking pronunciation, and engaging through comments. However, distractions, rapid content flow, and questionable material accuracy were identified as challenges. In conclusion, TikTok demonstrates strong potential as a supplementary learning tool that promotes autonomous, digitally literate, and engaging English learning when used critically and purposefully. These findings contribute to the growing body of MALL literature and highlight the significance of informal digital learning environments in contemporary language education.